Developing strategic leadership practices in the light of transparency and organizational citizenship behavior - A field study of a sample of the staff of the Office of the Inspector General at the Iraqi Ministry of Culture - الطائي, علي حسون; النقار, عبد الله حكمت (Journal of Economics and Administrative Sciences, 2012)
Diversity the terms and practice the organizational filed with different concepts and environment, which Iraqi environment part from them. Some organizational in Iraqi environment leave its basic oriented to agreement with the leader desire, their fore this research focus tow basic variable (organizational citizenship behavior & transparence), we supposition which is dependent to explanation the response variable (strategic leadership). The results justification in part and not justification in another part. For example the organizational citizenship behavior effect on some parte of the strategic leadership. The transparence have faraway to fly from the relation with organizational citizenship behavior and strategic leadership. We know this variables when we see it as shine for impact on practice of strategic leadership which is not enough. So that we shod be search to define another comprehensive variable or have related we can dependent to supporting public leadership performance level for organizational and put it in the right situation that aim to achievement what they do. In at all there are agreement between leadership and employee not only with emotion and thought but also by direction and purpose that will achieve intentionally.